Multiple antibiotic susceptibility of polyphosphate kinase mutants (ppk1 and ppk2) from Pseudomonas aeruginosa PAO1 as revealed by global phenotypic analysis - Javiera Ortiz-Severín; Macarena Varas; Catalina Bravo-Toncio; Nicolás Guiliani; Francisco P Chávez (Biological Research, 2015)
BACKGROUND: Pseudomonas aeruginosa is known to be a multidrug resistant opportunistic pathogen. Particularly, P. aeruginosa PAO1 polyphosphate kinase mutant (ppk1) is deficient in motility, quorum sensing, biofilm formation and virulence FINDINGS: By using Phenotypic Microarrays (PM) we analyzed near 2000 phenotypes of P. aeruginosa PAO1 polyP kinase mutants (ppk1 and ppk2). We found that both ppk mutants shared most of the phenotypic changes and interestingly many of them related to susceptibility toward numerous and different type of antibiotics such as Ciprofloxacin, Chloramphenicol and Rifampicin CONCLUSIONS: Combining the fact that ppk1 mutants have reduced virulence and are more susceptible to antibiotics, polyP synthesis and particularly PPK1, is a good target for the design of molecules with anti-virulence and anti-persistence properties.